Manganese-enhanced magnetic resonance imaging in Takotsubo syndrome. (3rd October 2022) - Singh, T; Joshi, S; Kersahw, L E; Baker, A H; Dawson, D K; Dweck, M R; Semple, S I; Newby, D E
Abstract: Background: Takotsubo syndrome is an increasingly common acute cardiac emergency characterised by profound transient left ventricular systolic dysfunction following a stressful event. Its pathophysiology remains poorly understood and a third of patients will have a major adverse cardiac or cerebrovascular event by 5 years [1]. Defective myocardial calcium homeostasis is central to contractile dysfunction and may be implicated in its pathophysiology. Manganese-enhanced magnetic resonance imaging is a novel non-invasive imaging technique that assesses myocardial manganese uptake as a measure of myocardial calcium handling [2]. Our aim was to investigate myocardial calcium handling using manganese-enhanced magnetic resonance imaging during the acute and recovery phase of takotsubo syndrome. Methods: This single centre case-controlled observational longitudinal cohort study was conducted in accordance with the Declaration of Helsinki and ethical committee approval with written informed consent. Twenty patients with takotsubo syndrome and 20 age, sex and cardiovascular risk factor matched volunteers were recruited between March 2020 and September 2021. Patients underwent gadolinium and manganese-enhanced magnetic resonance imaging during the index event with repeat manganese-enhanced magnetic resonance imaging after 3 months. Myocardial manganese uptake was characterised by Patlak modelling. Results: During the acute presentation, most patients had an "apical" pattern of takotsubo syndrome with reduced left ventricular ejection fraction (51±11 versus 67±8%, P<0.001, Figure 1), elevated left ventricular mass (89±11 versus 57±14 g/m 2, P<0.01) and native T1 (1358±49 versus 1211±28 ms, P<0.001) and T2 (60±7 versus 38±3 ms, P<0.001) values compared to matched volunteers. Patlak modelling demonstrated reduced myocardial manganese uptake (5.1±0.5 versus 8.0±1.0 mL/100g of tissue/min, P<0.0001) consistent with a major abnormality of myocardial calcium handling. Reduced myocardial manganese uptake attributable to apical takotsubo syndrome could be seen in one patient, scanned 18 days after symptom onset despite apparent resolution of cardiac function. Beyond 3 months of convalescence, left ventricular mass, ejection fraction, native T1 and T2 values were comparable to matched volunteers. Despite this, myocardial calcium handling remained abnormal compared to matched volunteers (6.7±0.7 versus 8.0±1.0 mL/100 g of tissue/min, P<0.001, Figure 2). Conclusions: In patients with takotsubo syndrome, there is a profound perturbation of myocardial calcium handling which is most marked acutely but persists after apparent recovery of left ventricular ejection fraction and resolution of myocardial oedema. Abnormal myocardial calcium handling is implicated in the pathophysiology of takotsubo syndrome and manganese-enhanced magnetic resonance imaging could play a major role in the diagnosis and risk stratification of patients with takotsubo syndrome. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Medical Research CouncilBritish Heart Foundation